Analisis Perubahan Waktu Pengeringan terhadap Variasi Tinggi Cerobong - Muhammad Syafrun; Syukri Himran; Wahyu Haryadi Piarah (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2018)
This study aims to find out the efficiency of grain dryers using a chimney and a fan as suction air from the collector into the drying chamber.The research was conducted at the Central of Laboratory Department of Mechanical Engineering Faculty of Engineering, University of Muslim Indonesia, Makassar. A dryer was made from a zinc plate of 0.2 mm as collector by using a hot-air and solar energy as a drying medium. It was expected that this tool can dry grain quickly with evenly distributed drying level or water content. There were five variations of the Chimney : 20 cm, 50 cm, 80 cm, 110 cm and 140 cm with the grain thickness of 7 cm, 5 cm and 3 cm. The data were then analyzed to obtained the efficiency of the dryer. The results reveal that the time required to lower the water content of the harvest grain from 24.6% to 13.6% - 13.85% of milled moisture was 4 hours - 6.5 hours with an efficiency of 34,232 % for grain thicknes 7 cm, 31,480 % for grain thicknes 5 cm and 30,122 for grain thicknes 3 cm at 80 cm chimney height.